Guest Satisfaction and Dissatisfaction with Pool Attributes at Five-Star Hotels in Dubai - István EGRESI; Vivien LUNGU (Studia Universitatis Babeş-Bolyai: Geographia, 2025)
Guest Satisfaction and Dissatisfaction with Pool Attributes at Five-Star Hotels in Dubai. This study investigates the influence of hotel amenities on guest satisfaction, with particular emphasis on swimming pool facilities in luxury hotels. The research employs a mixed-methods approach combining quantitative and qualitative content analysis of guest reviews from Booking.com to identify the key attributes of five-star hotel pools that most significantly affect guest satisfaction levels. The study focuses on Dubai as its research context, selected for its prominence in the global luxury tourism market. The emirate boasts 168 five-star hotels offering approximately 145,000 rooms and serviced apartments, including world-renowned properties such as the Burj Al Arab that serve as both accommodations and tourist destinations in their own right. The research revealed three primary dimensions of pools: “staff & service”, “pool environment” and “quality of pool”, alongside “overall impression”, each comprising multiple attributes. The results show that guests were the most satisfied with the quality of “staff and service” and the least satisfied with the “ambiance” (an attribute of the “pool environment”) and with the “quality of the pool”. These results have meaningful implications for hotel management practices and facility design considerations in the luxury hospitality sector.